Gamma knife thalamotomy for disabling tremor: a blinded evaluation - Lim, Shen Yang; Hodaie, M.; Fallis, M.; Poon, Y.Y.; Mazzella, F.; Moro, E. (American Medical Association, 2010)
Background: Gamma knife thalamotomy (GKT) has been used as a therapeutic option for patients with disabling tremor refractory to medications. Impressive improvement of tremor has been reported in the neurosurgical literature, but the reliability of such data has been questioned.